The Doctrine of Informed Consent and Duty of Disclosure: A Comparative Essay between the US, UK, Australia and Malaysia with Indonesia - Badli Esham, Alyssa Dalila (Indonesian Comparative Law Review, 2019)
The study aims to compare and contrast the position of four countries (The US, UK, Australia, and Malaysia) regarding informed consent, particularly on the subject of disclosure of information with Indonesia. Other than that, the legal issues to be studied were the implications brought upon the healthcare and judicial system in the respective countries as well as the advantages and disadvantages of each test propounded. It was found that previously the welfare of the patient in regards to their right to receive information (especially risks) regarding their medical treatment was only up to the discretion of the medical practitioner and other members of the medical profession, which eliminates liability against a negligent doctor if it was found that other members of the medical community would have done the same as him. It was not until the case of Rogers v Whitaker that the spectrum widened and allowed the courts to determine that whatever that should be disclosed to the patient must be something that the patient attaches significant risk to, this is then named the “Prudent Patient Test”, used by most countries in this study. The study finds that as an implication, most countries have departed from the previous paternalistic approach by doctors and as an advantage, encouraged individualism and the reduction of the patients as passive recipients in their own health care. Since most of the comparative countries are similar in application, it was found that the medical law envisioned and enforced in the respective countries was quite different compared to the civil legal system in Indonesia. Other than that, as a country that is highly ingrained with Islamic values of life, the perspective of human rights and individualism in Indonesia is distinct with most of the other countries studied.